IDENTIFIKASI LARVA NYAMUK DI DESA LAWANG URU KABUPATEN PULANG PISAU - Augustina, Indria; Palupi, Didin Retno Endah (Fakultas Kedokteran, Universitas Palangka Raya, 2023)
. In tropical nations like Indonesia, mosquitoes serve as carriers of viruses and parasites that can infect humans. Finding out which mosquito larvae species were present and where in Banama Tingang District—particularly in Lawang Uru Village—was the study's main goal. Descriptive survey research using simple random sampling methodology is what this study is. All of the mosquito larvae used in this study were collected from Lawang Uru Village. In residential areas, larvae are collected. Descriptive survey research using simple random sampling methodology is what this study is. All of the mosquito larvae used in this study were collected from Lawang Uru Village. In residential areas, larvae are collected. The study's findings revealed 232 larvae belonging to the following species: Culex quinquefasciatus, Aedes albopictus, Culex vishnui, and Aedes aegypti. utilized paint cans, tires, drums, boats, and livestock feeders were among the materials utilized to create larval breeding habitat in Lawang Uru Village.